Design and Characterization of Myristoylated and Non-Myristoylated Peptides Effective against Candida spp. Clinical Isolates - Bugli, Francesca; Massaro, Federica; Buonocore, Francesco; Saraceni, Paolo Roberto; Borocci, Stefano; Ceccacci, Francesca; Bombelli, Cecilia; Di Vito, Maura; Marchitiello, Rosalba; Mariotti, Melinda; Torelli, Riccardo; Sanguinetti, Maurizio; et al. (International journal of molecular sciences, 2022)
The increasing resistance of fungi to antibiotics is a severe challenge in public health, and newly effective drugs are required. Promising potential medications are lipopeptides, linear antimicrobial peptides (AMPs) conjugated to a lipid tail, usually at the N-terminus. In this paper, we investigated the in vitro and in vivo antifungal activity of three short myristoylated and non-myristoylated peptides derived from a mutant of the AMP Chionodracine. We determined their interaction with anionic and zwitterionic membrane-mimicking vesicles and their structure during this interaction. We then investigated their cytotoxic and hemolytic activity against mammalian cells. Lipidated peptides showed a broad spectrum of activity against a relevant panel of pathogen fungi belonging to Candida spp., including the multidrug-resistant C. auris. The antifungal activity was also observed vs. biofilms of C. albicans, C. tropicalis, and C. auris. Finally, a pilot efficacy study was conducted on the in vivo model consisting of Galleria mellonella larvae. Treatment with the most-promising myristoylated peptide was effective in counteracting the infection from C. auris and C. albicans and the death of the larvae. Therefore, this myristoylated peptide is a potential candidate to develop antifungal agents against human fungal pathogens.